2016
DOI: 10.1016/j.psyneuen.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability measure in breast cancer patients and survivors: A systematic review

Abstract: The heart rate variability analysis could be used as a complementary non-invasive tool for the early diagnosis and better prognosis of autonomic dysfunction, and survival in BC patients. There are many potential clinical applications of heart rate variability analysis in BC patients, and the employment of such approaches could lead to lower impairment of autonomic function in this individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 76 publications
(192 reference statements)
3
66
0
2
Order By: Relevance
“…The results of the study of Lončar-Turukalo et al [31] confirmed HRV alteration as an early marker of cardiotoxicity in DOX-induced cardiomyopathy in healthy rats. Since it is known that illness itself can provoke autonomic modulation [32], a rat model of colorectal cancer was applied in our study to reveal whether HRV changes can be used as a marker of DOX-induced cardiotoxicity in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study of Lončar-Turukalo et al [31] confirmed HRV alteration as an early marker of cardiotoxicity in DOX-induced cardiomyopathy in healthy rats. Since it is known that illness itself can provoke autonomic modulation [32], a rat model of colorectal cancer was applied in our study to reveal whether HRV changes can be used as a marker of DOX-induced cardiotoxicity in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the opinion of authors that the analysis of heart rate variability can be used as an important additional highly sensitive noninvasive tool in early diagnostics of cardiovascular diseases, improvement of autonomic dysfunction prognosis, survivability of patients, and other clinical applications, the discovered dependencies and the availability of standardized methods of registration and computation of the chosen heart rate variability indices allow to confirm the possibility of using the chosen heart rate variability indices as predictors of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with anthracyclines like doxorubicin, a class of chemotherapeutics commonly used in the treatment of breast cancer, are thought to lower HRV [82•]. Several studies reported an association between lower HRV and fatigue in breast cancer survivors [92]. Fagundes et al showed a lower resting-state HRV and higher norepinephrine levels in association with higher fatigue in breast cancer survivors.…”
Section: Neuroendocrine Function and Symptom Experiencementioning
confidence: 99%